Integration of ultrasound-electro-Fenton processes for total organic carbon and inorganic carbon removal in pharmaceutical wastewater - Hardyanti , Nurandani; Zaman , Badrus; Putri, Namira Fawzia; Dhea Phitaloka, Adinda Bella; Wahyuarta, Muhammad Bintang; Purwono, Purwono (Journal of Water and Land Development, 2026)
Pharmaceutical are widely used by humans and are commonly discharged into the environment as waste after use. Pharmaceutical wastewater contains organic compounds that can be removed through the integration of ultrasound and electro-Fenton methods. This study aims to analyse the removal efficiency of total organic carbon (TOC) and inorganic carbon (IC) in pharmaceutical wastewater using an integrated ultrasound-electro-Fenton process. Pharmaceutical wastewater obtained from PT. X was used for laboratory experiments. The independent variables in this study consisted of treatment time and pH in the ultrasound process. The ultrasound–electro-Fenton process was conducted using variations in treatment time, FeSO₄ + H₂O₂ dosage, and a voltage of 25 V. The optimal treatment condition was achieved at 90 minutes of ultrasound exposure and pH 3 under acidic conditions. At acidic pH, hydroxyl radicals (•OH) are formed through water dissociation during maximum cavitation, resulting in a TOC reduction of 71.48% and an IC reduction of 95.71%. The integrated process successfully reduced TOC by 94.04%. IC was also reduced by 98.27% after 90 minutes of treatment. These results demonstrate that the integrated ultrasound–electro-Fenton process is effective in reducing refractory organic compounds in pharmaceutical wastewater. The degradation of complex compounds increased biodegradability, as indicated by a decrease in biochemical oxygen demand (BOD) under acidic conditions. Further evaluation is needed for other parameters that may require additional treatment.